Adapting English Language Teaching to 21st Century Learners Through Kahoot Application - Tiofanny Elisabet Sirait; Tiondina Samosir; Tri Inda; Lihardo Manik; Dumaris E Silalahi (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2025)
This study explores the use of the Kahoot! application as a digital learning toolto enhance motivation, cooperation, and comprehension among vocational highschool students in English language teaching. As 21st-century learners,students today are digital natives who require interactive and technology-basedlearning environments. The research was conducted at SMK Swasta HKBPPematang Siantar using a qualitative descriptive approach. Data were collectedthrough classroom observation, documentation, and field notes. The resultsshowed that Kahoot! significantly increased students’ enthusiasm,participation, and teamwork during English lessons. Students were morefocused, cooperative, and motivated when learning through game-basedquizzes. Moreover, repeated quiz activities improved their understanding oflesson materials through active recall and feedback. Despite some technicalchallenges such as limited internet access and shared devices, the overalllearning atmosphere became more dynamic, joyful, and engaging. The studyconcludes that integrating Kahoot! into English teaching effectively supportsinteractive, fun, and student-centered learning for digital-age learners.Keyword : Kahoot! Application,English language teaching,Digitalnatives,Motivation,Game-based learning